Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1044/jshr.3703.583
|View full text |Cite
|
Sign up to set email alerts
|

Joint Book-Reading Strategies in Working-Class African American and White Mother-Toddler Dyads

Abstract: Twenty working-class mother-toddler dyads were videorecorded during three joint book-reading activities. Ten of the dyads were white, and 10 were African American, balanced for parent educational level, family income, and parental occupation. The children ranged in age from 18 to 30 months and were normally developing. The parents read an experimental book to their child two times and a favorite book they brought from home one time. Videotapes of the joint book-readings were analyzed to determine cultural diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
54
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 12 publications
5
54
0
2
Order By: Relevance
“…We also found that, when for parents literacy does not serve important personal needs, parents and children are less involved in meaning-related discussions that may make the book more understandable and enjoyable for young children. These parents do not initiate themes that go beyond the text, and they do not discuss how text relates to pictures to the same extent as other parents (Anderson-Yockel & Haynes, 1994;De Temple & Snow, 1996;Heath, 1983). They are also less inclined to change text in order to make it easier to comprehend.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that, when for parents literacy does not serve important personal needs, parents and children are less involved in meaning-related discussions that may make the book more understandable and enjoyable for young children. These parents do not initiate themes that go beyond the text, and they do not discuss how text relates to pictures to the same extent as other parents (Anderson-Yockel & Haynes, 1994;De Temple & Snow, 1996;Heath, 1983). They are also less inclined to change text in order to make it easier to comprehend.…”
Section: Discussionmentioning
confidence: 99%
“…Heath's (1983) ethnographic work has indeed suggested that IOW-SES African American caregivers do not use questions as much as IOW-SES White mothers. Using a quantitative methodology, subsequent studies (e.g., Anderson-Yockel & Haynes, 1994;Neuman, 1996) have shown that lowproficiency parent readers and their children were more likely to engage in book-focused interactions, compared with the interactions of more proficient parent readers who display more meaning-based interaction strategies. De Temple and Snow (1996) coded to what extent maternal utterances moved away from what could be seen on the page, including spontaneous connections to the child's own world.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Heath (1983) noted that, among African-Americans in the rural South, adults rarely elicited single-word nouns from preschool children, but they frequently sought comparisons, explanations, nonverbal responses, and information responses (in this order). Anderson-Yockel and Haynes (1994) reported that working-class African American mothers rarely asked questions, and their children produced more spontaneous verbalizations. Thus, a test task that requires naming single-word labels in response to adult questions may instead elicit longer responses such as explanations or descriptions.…”
mentioning
confidence: 99%
“…They seldom possessed picture books that were suitable for the ages of their children. Moreover, they perceived language as a unilateral way of conveying information in their communication with their children (Anderson-Yockel & Haynes, 1994). In addition, when they read picture books to their children, they seemed to give their children one-way explanations or simple answers when children asked questions .…”
Section: Introduction1mentioning
confidence: 99%